EFFECTS OF DIETARY SUPPLEMENTATION LEVELS OF TURMERIC POWDER(CURCUMA LONGA) ON PERFORMANCE, CARCASS CHARACTERISTICS AND GUT MICROFLORA IN BROILER CHICKENS - Hilal Ürüşan; Ş.Canan Bölükbaşı (Journal of Animal and Plant Sciences, 2017)
The study was conducted to determine the effect of turmeric powder at different levels (0, 2, 4, 6, 8, 10 g/ kg), and a single dose of chlortetracycline (10 mg/kg) to broiler diets on performance, carcass yield and gut microflora. The results revealed that adding 10 g/kg turmeric powder to the ration significantly decreased feed intake (FI). Meanwhile, adding 2 g/kg turmeric powder improved feed conversion ratio (FCR). Neither carcass yield nor weights of heart and liver organs were significantly affected by dietary treatments. The colony forming unit of lactic acid bacteria was found to be higher in the group of birds fed on the diet supplemented with 2 g/kg turmeric powder than the other groups of birds. While the highest E. coli content was determined in the birds received control diet and those received the diet added with 10 mg/kg antibiotic, the lowest E. coli content was determined in the groups of birds fed with the diets added with 6, 8 and 10 g/kg turmeric powder.In conclusion, increasing dieatry supplementation levels of turmeric powder, except for the 10 g/kg level has positive effects on bird’s performance and gutmicroflora. In particular, a level of 2 g/kg turmeric powder could be recommended as an alternative to feed antibiotics due to significantly improved FCR.
Keywords: Broiler chickens; turmeric powder (curcuma longa); performance; carcass yield; gut microflora